Structural basis of ZP2-targeted female nonhormonal contraception - Elisa Dioguardi; Alena Stsiapanava; Eileen Fahrenkamp; Ling Han; Daniele de Sanctis; José Inzunza; Luca Jovine (Proceedings of the National Academy of Sciences, 2025)
Monoclonal antibody IE-3 prevents mouse fertilization by binding ZP2, a major component of the oocyte-specific zona pellucida (ZP). We show that an IE-3-derived single-chain variable fragment (scFV) is sufficient for blocking fertilization in vitro and determine the structural basis of IE-3/ZP2 recognition. The high affinity of this interaction depends on induced fit of the epitope, offering insights for nonhormonal contraceptive design without off-target effects.